Relationship between dietary patterns and metabolic syndrome among urban populations in Ningxia, China - LI Hongyu; ZHANG Na; LI Lin; TAO Xiujuan; YANG Jianjun; ZHANG Yuhong; ZHAO Yi (浙江大学学报. 农业与生命科学版)
It is well documented that the role of dietary composition in relation to the development of metabolic syndrome (MS) remains inconclusive. Several studies on the relationship between MS and energy intake have suggested that the macronutrient composition of the diet (proteins, fats, carbohydrates) may play an important contributing role to MS in adults. So, this study aims to investigate the possible relationship between MS and energy intake, percentage energy intake from macronutrients among urban populations in Ningxia, China.According to different economic levels from 2011 to 2012, 2 465 subjects (age: 18-75 years) were selected using stratified cluster random sampling in Yinchuan, Wuzhong, Zhongwei, Guyuan, and Shizuishan in Ningxia, China. Dietary intake was assessed using 24-h food records and a validated food frequency questionnaire. Body mass, height, waist circumference, blood pressure, triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and blood glucose were measured. Logistic regression models were adjusted for age, smoking, drinking, and physical activity factors.The results showed that there were 647 MS cases in all subjects. According to the diagnosis criteria of MS, the incidence of MS was 26.2% (men: 281 cases (25%); women: 366 cases (27.3%)), no significant difference in sex composition (P>0.05). As a way of lifestyle, there was no significant difference in smoking, drinking, exercise between MS group and control group (P>0.05); significant difference was found in tertian dietary intake of protein and fat energy percentage between MS group and control group (P<0.05). Compared with control group, body mass index, waist circumference, systolic pressure (SBP), diastolic pressure (DBP), fasting plasma glucose (FPG), cholesterol (TC), TG, and low-density lipoprotein cholesterol (LDL-C) from MS group were significantly increased (P<0.05). After adjustment for age, gender, smoking, drinking and daily exercise levels, compared with the normal" dietary pattern, Logistic multifactor analysis indicated that the subjects with the high" protein energy intake to total energy intake had a higher odds ratio (OR) of high MS (OR: 1.417, 95% confidence interval (CI): 1.124-1.787), and the subjects with the high" fat energy intake to total energy intake had a higher OR of high MS (OR: 1.647, 95% CI: 1.239-2.190), and the subjects with the high" carbohydrate energy intake to total energy intake had a higher OR of high MS (OR: 1.810, 95% CI: 1.403-2.330).In sum, the evidence of an association between macronutrient intake and MS is found. Obviously, the subjects with the high" percentage of protein, fat, and carbohydrate energy intake to total energy intake excessive are the important risk factors of the MS in urban residents in Ningxia, China, so dietary intervention measures should be taken to prevent MS.